Production experiential knowledge student in higher education - Benítez Erice, Didiosky; Valdés Pardo, Víctor Giraldo; Questier, Frederik; Pérez Luján, Dalgys (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article refers to a research project developed in collaboration between the Universidad Central “Marta Abreu” de Las Villas (UCLV) in Cuba and the Free University of Brussels (VUB) in Belgium for the years 2010 to 2014, the auspices of the Flemish Interuniversity Council (VLIR), which was the culmination defending a doctoral thesis in Educational Sciences by the first author. The research project associated with this thesis was funded by VLIR - UOS (inter-university collaboration program with the Universidad Central “Marta Abreu” de Las Villas). This article reflecting a synthesis of the methodology used for the development of the research project and its findings exposed. The original document of the thesis is written in English.